Escherichia coli replication terminator protein impedes simian virus 40 (SV40) DNA replication fork movement and SV40 large tumor antigen helicase activity in vitro at a prokaryotic terminus sequence. - Bedrosian, C L (1991)
We have discovered that the Escherichia coli terminator protein (Ter) impedes replication fork movement, initiated in vitro from the simian virus 40 replication origin by the large tumor antigen (TAg), at the terminator site (tau R) of the prokaryotic plasmid R6K preferentially when tau R is present in one orientation with respect to the origin. We also have discovered that Ter impedes helicase activity of TAg at the tau R site, when tau R is in this same orientation. In contrast with Ter, a mutant EcoRI protein (EcoRIgln111) that binds with high affinity to but does not cleave at EcoRI recognition sequences impedes both simian virus 40 fork movement and the helicase activity of TAg in an EcoRI-site-orientation-independent manner. These results suggest that a feature common to both TAg and prokaryotic helicases may recognize the Ter-tau R complex resulting in a polarized pause in fork propagation and DNA unwinding. In contrast, the effect of EcoRIgln111-DNA complex on these reactions may be based on steric hindrance.